ANALISIS PENYELENGGARAAN PENDIDIKAN INKLUSI UNTUK PESERTA DIDIK BERKEBUTUHAN KHUSUS JENJANG SEKOLAH DASAR NEGERI DI JAKARTA BARAT - Aulia, Jaujatul; Asmiati, Neti; Mulia, Dedi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Inclusive education policies in Jakarta have been regulated, but their implementation in the field still faces challenges. Problems in implementing inclusive education in schools include limited understanding among educators, a lack of accessible facilities, and a lack of special assistant teachers. This study aims to analyze the implementation of inclusive education for students with special needs at public elementary schools in West Jakarta. The UNS Inclusion Metric was used as a reference in analyzing the implementation of inclusive education for students with special needs in schools. This study was conducted in three schools, namely SDN Kapuk 15 Pagi, SDN Kapuk 01 Pagi, and SDN Kapuk 12 Petang, using a mixed method approach through the distribution of attitude assessment instruments as well as observation, interviews, and documentation. The results showed that the attitudes of school members towards inclusive education were in the fairly good category, with an average score of 29.75 out of 36, which indicates a positive attitude towards students with special needs. However, the implementation of inclusive education has not been optimal. The LED results revealed limitations in institutional aspects, a lack of GPK, the unavailability of SOPs for inclusive learning, a lack of psychological services, and the unavailability of accessible facilities. Overall, the school has an attitude that supports inclusion, but it is necessary to strengthen teacher competencies, provide support services, and improve policies and infrastructure so that inclusive education can be implemented effectively and sustainably.